Riding the Rhythm of Melatonin Through Pregnancy to Deliver on Time - McCarthy, Ronald; Jungheim, Emily S.; Fay, Justin C.; Bates, Keenan; Herzog, Erik D.; England, Sarah K. (Frontiers in Endocrinology, 2019)
Reproductive function is regulated by the circadian (“circa” or approximately; diēm or day) system, which coordinates physiology and behavior with predictable daily changes in the environment such as light/dark cycles. For example, most species deliver around a particular time of day. In mammals, circadian rhythms are controlled by the master circadian pacemaker, the suprachiasmatic nucleus. One key way that the suprachiasmatic nucleus coordinates circadian rhythms throughout the body is by regulating production of the sleep-promoting hormone melatonin. Serum melatonin concentration, which peaks at night and is suppressed during the day, is one of the best biological indicators of circadian timing. Here, we review evidence supporting the idea that melatonin helps regulate the maternal and fetal circadian systems and contributes to regulating birth timing. Finally, we discuss the potential for melatonin-based therapeutic strategies to alleviate poor pregnancy outcomes such as preeclampsia and preterm birth.